Conditioned inhibition in preweanling rats - Aranda-Fernandez, Patricio E. (2016)
Inhibitory conditioning is a very well established phenomenon in associative learning that has been demonstrated in both humans and adult animals. But in spite of the fact that this topic has generated much empirical and theoretical work, there are no published studies assessing inhibitory learning during the early ontogeny of the rat. In this study we test the possibility of finding conditioned inhibition in infant rats (Day 10) using a conditioned taste aversion procedure. We tested whether the consumption of saccharin (A) was reduced when paired with a LiCl injection compared to the presentation of saccharin in compound with a lemon odor (AX) without any aversive consequence. After training, retardation, and summation tests were conducted in order to evaluate the inhibitory properties of the lemon odor (X). The results of this study showed that in male pups, after conditioned inhibition training, stimulus X passed both retardation and summation tests. These results indicate that conditioned inhibition can be established in the early development of the rat, suggesting that animals at this stage of ontogeny have the capacity to acquire and to express inhibitory conditioning, although this effect appears to be sex-dependent.